2020
DOI: 10.24071/jpsc.002408
|View full text |Cite
|
Sign up to set email alerts
|

Association Between Smoking Behaviour and Glycohemoglobine Levels Among Adult Javanese Indonesian Smokers

Abstract: Nicotine, the active compound in cigarettes, can cause impaired glucose metabolism by increasing insulin resistance as well as decreasing insulin secretion in β cell pancreas. This condition can increase the risk of type 2 diabetes in human. This study aims to evaluate the effect of smoking behaviour, determined by Cigarette per Day (CPD) and smoking duration, on glychohemoglobine (HbA1c) levels of Javanese Indonesian smokers. 30 smokers were studied consisting of 7 smokers with <10 CPD, 19 smokers with 11-… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
5
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5

Relationship

3
2

Authors

Journals

citations
Cited by 5 publications
(7 citation statements)
references
References 39 publications
2
5
0
Order By: Relevance
“…According to the characteristic data shown in Table 1, related to the average number of cigarettes per day (13.5±4.4 sticks) and smoking duration (23.2±4.8 years) of the respondents, all of the respondents are associated as addictive smokers affecting the increase in LDL-C levels. So, it is in line with another study that the chronic effect of smoking behavior would arise when individuals consume more than 20 cigarettes per day and 25 years minimum smoking duration (Patramurti and Fenty, 2020).…”
Section: Resultssupporting
confidence: 88%
“…According to the characteristic data shown in Table 1, related to the average number of cigarettes per day (13.5±4.4 sticks) and smoking duration (23.2±4.8 years) of the respondents, all of the respondents are associated as addictive smokers affecting the increase in LDL-C levels. So, it is in line with another study that the chronic effect of smoking behavior would arise when individuals consume more than 20 cigarettes per day and 25 years minimum smoking duration (Patramurti and Fenty, 2020).…”
Section: Resultssupporting
confidence: 88%
“…Furthermore, we indicated that the prediabetes condition would arise at a minimum CPD of 20 cigarettes and a minimum smoking duration of 25 years. While, the diabetes condition will appear at a minimum CPD of 20 cigarettes with a minimum smoking duration of 29 years (Patramurti and Fenty, 2020). Based on the data presented in Table 1 above, it saw that 91.3% (17.4% smoked < 10 and 93.9% smoked 11-20) of participants have only smoked less than 20 cigarettes per day.…”
Section: Results and Discusionmentioning
confidence: 99%
“…In the previous study, we revealed that smoking behavior could affect glycohemoglobin levels (HbA1c) (Patramurti and Fenty, 2020). There has been demonstrating that the number of cigarettes smoked, and the length of smoking activity will increase the HbA1c level that leading to a high risk for suffering T2DM.…”
Section: Results and Discusionmentioning
confidence: 99%
“…We have also reported that smoking can increase diabetes risk factors. Prediabetes was developing in smokers who had smoked for at least 25 years with 25 cigarettes per day 16 . Furthermore, in our recent study on diabetic patients, both smokers and non-smokers, high-frequency CYP2A6*4, the inactive allele gene of CYP2A6, was detected 17 .…”
Section: Introductionmentioning
confidence: 99%